2023
DOI: 10.3390/microorganisms11102595
|View full text |Cite
|
Sign up to set email alerts
|

Biofilms as Battlefield Armor for Bacteria against Antibiotics: Challenges and Combating Strategies

Sara Bano,
Noor Hassan,
Muhammad Rafiq
et al.

Abstract: Bacterial biofilms are formed by communities, which are encased in a matrix of extracellular polymeric substances (EPS). Notably, bacteria in biofilms display a set of ‘emergent properties’ that vary considerably from free-living bacterial cells. Biofilms help bacteria to survive under multiple stressful conditions such as providing immunity against antibiotics. Apart from the provision of multi-layered defense for enabling poor antibiotic absorption and adaptive persistor cells, biofilms utilize their extrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 157 publications
0
4
0
Order By: Relevance
“…Bacteria employ quorum sensing, a process involving chemical signaling molecules, to coordinate biofilm formation and antibiotic resistance based on population density and environmental cues . The intricate interplay among antibiotic concentration, bacterial genetics, environmental factors, and communication systems within bacterial populations contributes to the variability observed in biofilm production following antibiotic exposure …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bacteria employ quorum sensing, a process involving chemical signaling molecules, to coordinate biofilm formation and antibiotic resistance based on population density and environmental cues . The intricate interplay among antibiotic concentration, bacterial genetics, environmental factors, and communication systems within bacterial populations contributes to the variability observed in biofilm production following antibiotic exposure …”
Section: Resultsmentioning
confidence: 99%
“…51 The intricate interplay among antibiotic concentration, bacterial genetics, environmental factors, and communication systems within bacterial populations contributes to the variability observed in biofilm production following antibiotic exposure. 2 This variability highlights the complexity of managing biofilm-related infections and underscores the need for a comprehensive approach to combat antibiotic resistance. 52 AgNP therapy may be one such approach, as in this study, they have shown the capacity to mitigate biofilm formation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacteria encased in a matrix are known as biofilm 16 . The matrix protects the bacteria from chemical assaults and, as such, poses a serious challenge for antibiotic treatment 17 . Biofilm formation is essential for root colonization 15,18 .…”
Section: Introductionmentioning
confidence: 99%